Special ion bipolar exchange membrane and preparation method thereof
By building a gradient transition layer and nanofiber network, combining photoelectric functional coating and bionic flow channel, the problems of energy loss and short life of traditional bipolar membranes are solved, and efficient and reliable bipolar membrane operation is achieved.
Patent Information
- Application Number
- CN202510409974.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-08-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional bipolar membranes have high ion migration impedance and large energy losses due to the lack of transition structure of heterogeneous materials interfaces, and high-temperature operation can easily cause membrane layer layering. The static cross-linking network cannot automatically repair microscopic damage, resulting in short film life and frequent maintenance.
The perfluorosulfonic acid cation exchange membrane and the quaternized polyether ether ketone anion exchange membrane are used as substrates, and a nanoscale porous structure is constructed through plasma treatment, a gradient transition layer is introduced and electrospinned to form a nanofiber network, and two-dimensional boron nitride nanosheets are added to cross-link, combining photoelectric functional coatings and bionic fractal flow channels to achieve a self-healing composite membrane.
It significantly reduces energy loss, improves mechanical stability and high-temperature operation reliability, extends the life of membrane modules, reduces maintenance frequency and cost, and improves processing efficiency and sealing.
Smart Images

Figure CN120515262A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ion bipolar exchange membranes, and specifically relates to a special ion bipolar exchange membrane and a preparation method thereof. Background Art
[0002] As a highly efficient and environmentally friendly membrane separation process, electrodialysis technology is widely used in seawater desalination, wastewater treatment, food and pharmaceutical purification, and acid and alkali preparation. The performance of its core component, the ion exchange membrane, directly determines the system's energy efficiency and stability. Bipolar membranes, as specialized ion exchange membranes, can directly convert salts into acids and alkalis through water dissociation, making them of great value in resource recovery and clean production.
[0003] However, existing bipolar membranes have significant defects: the lack of transition structure at the interface of traditional heterogeneous materials leads to high ion migration impedance and large energy loss, and high-temperature operation easily causes membrane delamination; the static cross-linked network cannot autonomously repair micro-damage, resulting in a short membrane life and frequent maintenance. Summary of the Invention
[0004] The purpose of the present invention is to provide a special ion bipolar exchange membrane and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a method for preparing a special ion bipolar exchange membrane, the method comprising:
[0006] S1: Perfluorosulfonic acid cation exchange membrane and quaternized polyetheretherketone anion exchange membrane are used as substrates. A nano-scale porous structure is constructed on the surface of the cation exchange membrane through plasma treatment, and a fluorinated silane coupling agent is grafted on the surface of the anion exchange membrane.
[0007] S2: A gradient transition layer is introduced between the positive membrane and the negative membrane, and an electrospinning technique is used to prepare a nanofiber interwoven network containing sulfonic acid groups and quaternary ammonium groups to form an ion conduction bridge.
[0008] S3: Two-dimensional boron nitride nanosheets are evenly dispersed in the transition layer and cross-linked with ionic groups through hydrogen bonding to improve the mechanical strength and thermal stability of the membrane stack.
[0009] S4: Place the three-layer structure of positive film-transition layer-negative film in a vacuum hot press, inject polysiloxane prepolymer containing double-ended epoxy groups, and achieve chemical bonding to form a self-healing composite membrane.
[0010] S5: Functional coatings of sulfonated carbon quantum dots and phosphotungstic acid-doped polyaniline are sprayed on both sides of the composite membrane to reduce the water dissociation voltage through the photoelectric synergistic effect.
[0011] S6: Femtosecond laser etching technology is used to prepare bionic fractal flow channels on the membrane surface, combined with a micron-scale honeycomb support grid to improve the membrane stack flux.
[0012] S7: The composite membrane was immersed in an ethanol solution containing triethylenetetramine to induce secondary cross-linking, and then washed alternately with hydrochloric acid and sodium hydroxide to activate the ion exchange sites.
[0013] S8: The performance of the composite membrane in the electrodialysis system was tested using an online electrochemical workstation and finally encapsulated in a titanium alloy frame with a silicone sealing ring.
[0014] In a preferred embodiment, in step S1, a perfluorosulfonic acid cation exchange membrane and a quaternized polyetheretherketone anion exchange membrane are used as the base materials. The cation exchange membrane is subjected to plasma treatment, with the treatment power controlled at 80 to 120 watts and the treatment time being 5 to 8 minutes, to generate a uniform porous structure with a pore size of 20 to 50 nanometers on the membrane surface to improve the ion selective transmission efficiency. The surface of the anion exchange membrane is grafted with a fluorinated silane coupling agent by an immersion method, with a solution concentration of 0.5% to 1.5%, a treatment temperature of 45 to 55 degrees Celsius, and a reaction time of 30 to 60 minutes to enhance the interfacial chemical stability and reduce the contact resistance between the membrane layers. After treatment, the membrane surface needs to be rinsed three times with deionized water to remove unreacted residual reagents.
[0015] In a preferred embodiment, in step S2, a gradient transition layer is prepared between the cation membrane and the anion membrane using electrospinning technology. The spinning solution is composed of a mixture of 8% to 12% polyacrylonitrile solution and 2% to 4% polyvinyl alcohol, with a gradient transition of the mass ratio of sulfonic acid groups to quaternary ammonium groups from 5:1 on the cation membrane side to 1:5 on the anion membrane side. The electrospinning voltage is set at 15,000 to 20,000 volts, the receiving distance is 10 to 15 cm, and the fiber diameter is controlled to be 80 to 150 nanometers. The thickness of the transition layer is adjusted to 100 to 200 nanometers by deposition time, forming a continuous three-dimensional nanofiber network structure, which provides an ion-conducting bridge between the cation membrane and the anion membrane.
[0016] In a preferred embodiment, in step S3, two-dimensional boron nitride nanosheets with lateral dimensions of 300 to 500 nanometers are dispersed in the transition layer material at a doping ratio of 0.5% to 1.5%. Ultrasound-assisted mixing is employed with an ultrasonic power of 200 to 300 watts and a treatment time of 30 to 45 minutes to ensure uniform distribution of the nanosheets. The composite film is then vacuum-dried at 60 to 80 degrees Celsius for 4 to 6 hours to form a cross-linked network between the boron nitride nanosheets and the sulfonic acid and quaternary ammonium groups through hydrogen bonding. This ultimately increases the tensile strength of the composite film to over 40 MPa and allows it to withstand high temperatures of 60 degrees Celsius.
[0017] In a preferred embodiment, in step S4, the three-layer structure (cation film, transition layer, and cathodic film) is placed in a vacuum hot press at a temperature of 115 to 125 degrees Celsius, a pressure of 0.4 to 0.6 MPa, and a duration of 20 to 30 minutes. A polysiloxane prepolymer containing double-ended epoxy groups is simultaneously injected at a concentration of 3% to 5%, forming covalent crosslinks through interfacial condensation reactions. After crosslinking, the composite membrane exhibits an elongation at break exceeding 150%, and microcracks can be self-healed by heating at 80 degrees Celsius for 10 minutes, with a repair efficiency exceeding 90%.
[0018] In a preferred embodiment, in step S5, the cation side of the composite membrane is coated with a sulfonated carbon quantum dot coating using a spraying process at a rate of 0.2 to 0.4 ml / min, with a coating thickness of 10 to 30 microns. The cathodic side is sprayed with a phosphotungstic acid-doped polyaniline solution at a doping ratio of 1:0.5 to 1:1. After spraying, the membrane is dried at 50 to 70 degrees Celsius for 2 to 4 hours. This functional coating generates photogenerated carriers under visible light irradiation, reducing the water dissociation voltage from 0.83 volts for conventional membranes to 0.68 volts, while also suppressing concentration polarization.
[0019] In a preferred embodiment, in step S6, a femtosecond laser is used to micro-process the membrane surface, with a laser wavelength of 1030 nanometers, a pulse energy of 50 to 100 microjoules, and a repetition rate of 1,000 to 5,000 hertz. Fractal tree-like flow channels with a depth of 50 to 100 microns and a width of 200 to 500 microns are etched, with branching angles of 60 to 90 degrees. Simultaneously, a hexagonal honeycomb support grid with a porosity of over 85% is prepared, with a grid cell size of 500 to 800 microns. This structure increases the membrane stack flux by 30% and reduces the operating pressure difference to 60% of that of conventional membranes.
[0020] In a preferred embodiment, in step S7, the composite membrane is immersed in an ethanol solution containing 1% triethylenetetramine at a constant temperature of 55 to 65 degrees Celsius for 1.5 to 2.5 hours to induce secondary crosslinking between the amino groups and the residual epoxy groups. The membrane is then rinsed three times with alternating 0.5 mol / L hydrochloric acid and sodium hydroxide solutions, each rinse lasting 5 to 10 minutes, to activate the ion exchange groups and remove impurities. The membrane surface has an absolute value of zeta potential greater than 30 mV and an ion exchange capacity of 1.8 to 2.2 milliequivalents / g after treatment.
[0021] In a preferred embodiment, in step S8, the composite membrane was loaded into a three-compartment electrodialysis apparatus for testing using a 1 mol / L sodium chloride solution, an operating voltage of 25 volts, a current density of 50 milliamperes per square centimeter, and an operating temperature of 35 degrees Celsius. The measured current efficiency was 95% to 98%, the water dissociation voltage was stable at 0.68 to 0.72 volts, and the membrane resistance increased by less than 5% after 500 hours of continuous operation. Finally, the membrane was placed in a titanium alloy frame and sealed with a 0.5 to 1 mm thick silicone seal. The frame bolts were torqued to 2 to 3 Nm to ensure long-term leak-free operation.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0023] 1. The present invention effectively addresses the energy loss problem of traditional bipolar membranes caused by the interface impedance of heterogeneous materials through the use of gradient transition layer construction technology. The three-dimensional nanofiber network formed by electrospinning significantly shortens the ion migration path. Combined with the reinforcing effect of boron nitride nanosheets, this not only significantly improves the mechanical stability of the membrane stack but also enhances operational reliability in high-temperature environments. The introduction of a dynamic cross-linked network imparts self-healing properties to the membrane material, enabling it to autonomously repair microscopic damage generated during operation, significantly extending the service life of the membrane assembly and reducing maintenance frequency and costs in industrial scenarios.
[0024] 2. In the present invention, the combination of bionic fractal flow channel design and optoelectronic functional coating creates a new model of efficient mass transfer and energy-saving operation. The fractal structure of the fluid channel optimizes the uniformity of material distribution, which essentially improves the processing efficiency of the membrane stack. The optoelectronic synergistic effect coating effectively reduces the energy threshold of the water dissociation process through the combination of new materials, providing a more economical solution for high-energy consumption scenarios such as acid and alkali preparation. The innovative design of the packaging process ensures the sealing and corrosion resistance of the membrane assembly in long-term operation, providing reliable guarantees for continuous operation in industrial wastewater treatment, resource recovery and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic structural diagram of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0027] Example:
[0028] Reference Figure 1 ,
[0029] A method for preparing a special ion bipolar exchange membrane, comprising:
[0030] S1: Perfluorosulfonic acid cation exchange membrane and quaternized polyetheretherketone anion exchange membrane are used as substrates. A nano-scale porous structure is constructed on the surface of the cation exchange membrane through plasma treatment, and a fluorinated silane coupling agent is grafted on the surface of the anion exchange membrane.
[0031] S2: A gradient transition layer is introduced between the positive membrane and the negative membrane, and an electrospinning technique is used to prepare a nanofiber interwoven network containing sulfonic acid groups and quaternary ammonium groups to form an ion conduction bridge.
[0032] S3: Two-dimensional boron nitride nanosheets are evenly dispersed in the transition layer and cross-linked with ionic groups through hydrogen bonding to improve the mechanical strength and thermal stability of the membrane stack.
[0033] S4: Place the three-layer structure of positive film-transition layer-negative film in a vacuum hot press, inject polysiloxane prepolymer containing double-ended epoxy groups, and achieve chemical bonding to form a self-healing composite membrane.
[0034] S5: Functional coatings of sulfonated carbon quantum dots and phosphotungstic acid-doped polyaniline are sprayed on both sides of the composite membrane to reduce the water dissociation voltage through the photoelectric synergistic effect.
[0035] S6: Femtosecond laser etching technology is used to prepare bionic fractal flow channels on the membrane surface, combined with a micron-scale honeycomb support grid to improve the membrane stack flux.
[0036] S7: The composite membrane was immersed in an ethanol solution containing triethylenetetramine to induce secondary cross-linking, and then washed alternately with hydrochloric acid and sodium hydroxide to activate the ion exchange sites.
[0037] S8: The performance of the composite membrane in the electrodialysis system was tested using an online electrochemical workstation and finally encapsulated in a titanium alloy frame with a silicone sealing ring.
[0038] In step S1, perfluorosulfonic acid cation exchange membrane and quaternized polyetheretherketone anion exchange membrane are used as the base materials. The cation exchange membrane is plasma treated with a processing power of 80 to 120 watts and a treatment time of 5 to 8 minutes to generate a uniform porous structure with a pore size of 20 to 50 nanometers on the membrane surface to improve the ion selective transmission efficiency. The surface of the anion exchange membrane is grafted with a fluorinated silane coupling agent by an immersion method with a solution concentration of 0.5% to 1.5%, a treatment temperature of 45 to 55 degrees Celsius, and a reaction time of 30 to 60 minutes to enhance the interfacial chemical stability and reduce the contact resistance between the membrane layers. After treatment, the membrane surface needs to be rinsed three times with deionized water to remove unreacted residual reagents.
[0039] In step S2, a gradient transition layer is prepared between the cation and anion membranes using electrospinning technology. The spinning solution is composed of a mixture of 8% to 12% polyacrylonitrile solution and 2% to 4% polyvinyl alcohol. The mass ratio of sulfonic acid groups to quaternary ammonium groups gradually transitions from 5:1 on the cation side to 1:5 on the anion side. The electrospinning voltage is set at 15,000 to 20,000 volts, the receiving distance is 10 to 15 cm, and the fiber diameter is controlled between 80 and 150 nanometers. The thickness of the transition layer is adjusted to 100 to 200 nanometers by deposition time, forming a continuous three-dimensional nanofiber network structure, which provides an ion-conducting bridge between the cation and anion membranes.
[0040] In step S3, two-dimensional boron nitride nanosheets with lateral dimensions of 300 to 500 nanometers are dispersed in the transition layer material at a doping ratio of 0.5% to 1.5%. Ultrasonic-assisted mixing is used with an ultrasonic power of 200 to 300 watts for 30 to 45 minutes to ensure uniform distribution of the nanosheets. The material is then vacuum-dried at 60 to 80 degrees Celsius for 4 to 6 hours, allowing the boron nitride nanosheets to form a cross-linked network with sulfonic acid groups and quaternary ammonium groups through hydrogen bonds. This ultimately increases the tensile strength of the composite film to over 40 MPa and allows it to withstand high temperatures of 60 degrees Celsius.
[0041] In step S4, the three-layer structure (cation film, transition layer, and cathodic film) is placed in a vacuum hot press at a temperature of 115 to 125 degrees Celsius, a pressure of 0.4 to 0.6 MPa, and a duration of 20 to 30 minutes. Simultaneously, a polysiloxane prepolymer containing double-ended epoxy groups is injected at a concentration of 3% to 5%, forming covalent crosslinks through interfacial condensation reactions. After crosslinking, the composite membrane exhibits an elongation at break exceeding 150%, and microcracks can be self-healed by heating at 80 degrees Celsius for 10 minutes, with a repair efficiency exceeding 90%.
[0042] In step S5, the cation side of the composite membrane is coated with a sulfonated carbon quantum dot coating using a spraying process at a rate of 0.2 to 0.4 ml / min, with a coating thickness of 10 to 30 microns. The cathodic side is sprayed with a phosphotungstic acid-doped polyaniline solution at a doping ratio of 1:0.5 to 1:1. After spraying, the membrane is dried at 50 to 70 degrees Celsius for 2 to 4 hours. This functional coating generates photogenerated carriers under visible light irradiation, reducing the water dissociation voltage from 0.83 volts for conventional membranes to 0.68 volts, while also suppressing concentration polarization.
[0043] In step S6, the membrane surface is micro-machined using a femtosecond laser with a laser wavelength of 1030 nanometers, a pulse energy of 50 to 100 microjoules, and a repetition rate of 1,000 to 5,000 hertz. Fractal tree-like channels with a depth of 50 to 100 microns and a width of 200 to 500 microns are etched, with branching angles of 60 to 90 degrees. Simultaneously, a hexagonal honeycomb support grid with a porosity of over 85% is prepared, with a grid cell size of 500 to 800 microns. This structure increases the membrane stack flux by 30% and reduces the operating pressure difference to 60% of that of traditional membranes.
[0044] In step S7, the composite membrane is immersed in an ethanol solution containing 1% triethylenetetramine at a constant temperature of 55 to 65 degrees Celsius for 1.5 to 2.5 hours to induce secondary crosslinking between the amino groups and the residual epoxy groups. The membrane is then rinsed three times with alternating 0.5 mol / L hydrochloric acid and sodium hydroxide solutions, each rinse lasting 5 to 10 minutes, to activate the ion exchange groups and remove impurities. The absolute value of the zeta potential of the treated membrane surface is greater than 30 millivolts, and the ion exchange capacity reaches 1.8 to 2.2 milliequivalents / g.
[0045] In step S8, the composite membrane was installed in a three-compartment electrodialysis apparatus for testing using a 1 mol / L sodium chloride solution, an operating voltage of 25 V, a current density of 50 mA / cm², and an operating temperature of 35°C. The measured current efficiency was 95% to 98%, the water dissociation voltage was stable at 0.68 to 0.72 V, and the membrane resistance increased by less than 5% after 500 hours of continuous operation. Finally, the membrane was placed in a titanium alloy frame and sealed with a 0.5 to 1 mm thick silicone seal. The frame bolts were torqued to 2 to 3 Nm to ensure long-term leak-free operation.
[0046] From the above we can know:
[0047] In this invention, the gradient transition layer construction technology effectively solves the energy loss problem caused by the interface impedance of heterogeneous materials in traditional bipolar membranes. The three-dimensional nanofiber network formed by electrospinning significantly shortens the ion migration path. Combined with the reinforcing effect of boron nitride nanosheets, it not only greatly improves the mechanical stability of the membrane stack, but also enhances its operational reliability in high-temperature environments. The introduction of a dynamic cross-linked network gives the membrane material self-healing properties, which can autonomously repair microscopic damage caused during operation, significantly extending the service life of the membrane assembly and reducing the frequency and cost of maintenance in industrial scenarios.
[0048] In the present invention, the combination of bionic fractal flow channel design and optoelectronic functional coating has created a new model of efficient mass transfer and energy-saving operation. The fluid channel with a fractal structure optimizes the uniformity of material distribution, which essentially improves the processing efficiency of the membrane stack. The optoelectronic synergistic effect coating effectively reduces the energy threshold of the water dissociation process through a combination of new materials, providing a more economical solution for high-energy consumption scenarios such as acid and alkali preparation. The innovative design of the packaging process ensures the sealing and corrosion resistance of the membrane assembly in long-term operation, providing reliable guarantees for continuous operation in industrial wastewater treatment, resource recovery and other fields.
[0049] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0050] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A method for preparing a special ion bipolar exchange membrane, characterized in that: The method comprises: S1: Using perfluorosulfonic acid cation exchange membrane and quaternized polyetheretherketone anion exchange membrane as substrates, a nano-scale porous structure is constructed on the surface of the cation exchange membrane through plasma treatment, and a fluorinated silane coupling agent is grafted on the surface of the anion exchange membrane; S2: A gradient transition layer is introduced between the cation membrane and the anion membrane, and an electrospinning technique is used to prepare a nanofiber interwoven network containing sulfonic acid groups and quaternary ammonium groups to form an ion conduction bridge; S3: Uniformly disperse two-dimensional boron nitride nanosheets in the transition layer and cross-link with ionic groups through hydrogen bonding to improve the mechanical strength and thermal stability of the membrane stack; S4: The three-layer structure of the cation film, transition layer, and anion film is placed in a vacuum hot press, and a polysiloxane prepolymer containing double-ended epoxy groups is injected to achieve chemical bonding to form a self-healing composite membrane; S5: Functional coatings of sulfonated carbon quantum dots and phosphotungstic acid-doped polyaniline are sprayed on both sides of the composite membrane to reduce the water dissociation voltage through the photoelectric synergistic effect; S6: Femtosecond laser etching technology is used to create biomimetic fractal flow channels on the membrane surface, combined with a micron-scale honeycomb support grid to improve the membrane stack flux; S7: The composite membrane was immersed in an ethanol solution containing triethylenetetramine to induce secondary cross-linking, and then washed alternately with hydrochloric acid and sodium hydroxide to activate the ion exchange sites; S8: The performance of the composite membrane in the electrodialysis system was tested using an online electrochemical workstation and finally encapsulated in a titanium alloy frame with a silicone sealing ring.
2. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S1, a perfluorosulfonic acid cation exchange membrane and a quaternized polyetheretherketone anion exchange membrane are used as base materials; the cation exchange membrane is subjected to plasma treatment, the treatment power is controlled at 80 to 120 watts, and the treatment time is 5 to 8 minutes, to generate a uniform porous structure with a pore size of 20 to 50 nanometers on the membrane surface to improve the ion selective transmission efficiency; a fluorinated silane coupling agent is grafted onto the surface of the anion exchange membrane by an immersion method, the solution concentration is 0.5% to 1.5%, the treatment temperature is 45 to 55 degrees Celsius, and the reaction time is 30 to 60 minutes to enhance the interfacial chemical stability and reduce the contact resistance between the membrane layers; after treatment, the membrane surface needs to be rinsed three times with deionized water to remove unreacted residual reagents.
3. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S2, a gradient transition layer is prepared between the cation membrane and the cathode membrane by electrospinning technology; the spinning solution is composed of a mixture of a polyacrylonitrile solution with a mass fraction of 8% to 12% and a polyvinyl alcohol with a mass fraction of 2% to 4%, wherein the mass ratio of sulfonic acid groups to quaternary ammonium groups is gradiently transitioned from 5:1 on the cation membrane side to 1:5 on the cathode membrane side; the electrospinning voltage is set to 15,000 to 20,000 volts, the receiving distance is 10 to 15 centimeters, and the fiber diameter is controlled to be 80 to 150 nanometers; the thickness of the transition layer is adjusted to 100 to 200 nanometers by deposition time, forming a continuous three-dimensional nanofiber network structure, realizing an ion conduction bridge between the cation membrane and the cathode membrane.
4. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S3, two-dimensional boron nitride nanosheets with a lateral size of 300 to 500 nanometers are dispersed in the transition layer material with a doping ratio of 0.5% to 1.5%. Ultrasonic assisted mixing technology is used with an ultrasonic power of 200 to 300 watts and a processing time of 30 to 45 minutes to ensure uniform distribution of the nanosheets. Subsequently, vacuum drying is performed at 60 to 80 degrees Celsius for 4 to 6 hours to form a cross-linked network between the boron nitride nanosheets and sulfonic acid groups and quaternary ammonium groups through hydrogen bonds, ultimately increasing the tensile strength of the composite membrane to above 40 MPa and allowing it to withstand a high temperature environment of 60 degrees Celsius.
5. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S4, the three-layer structure of the positive film-transition layer-negative film is placed in a vacuum hot press at a hot pressing temperature of 115 to 125 degrees Celsius, a pressure of 0.4 to 0.6 MPa, and a duration of 20 to 30 minutes; a polysiloxane prepolymer containing a double-ended epoxy group is simultaneously injected with a concentration controlled at 3% to 5% to form covalent crosslinks through an interfacial condensation reaction; after crosslinking is completed, the elongation at break of the composite membrane exceeds 150%, and microcracks can be self-repaired by heating at 80 degrees Celsius for 10 minutes, with a repair efficiency of more than 90%.
6. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S5, a sulfonated carbon quantum dot coating is applied to the anode side of the composite membrane using a spraying process, with a spraying rate of 0.2 to 0.4 ml / min and a coating thickness of 10 to 30 μm; a polyaniline solution doped with phosphotungstic acid is sprayed on the cathode side of the composite membrane, with a doping ratio of 1:0.5 to 1:1, and the membrane is dried at 50 to 70 degrees Celsius for 2 to 4 hours after spraying; the functional coating enables the membrane to generate photogenerated carriers under visible light irradiation, reducing the water dissociation voltage from 0.83 volts of a conventional membrane to 0.68 volts, while suppressing concentration polarization.
7. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S6, a femtosecond laser is used to micro-process the membrane surface, with a laser wavelength of 1030 nanometers, a pulse energy of 50 to 100 microjoules, and a repetition frequency of 1,000 to 5,000 hertz; a fractal tree-like flow channel with a depth of 50 to 100 microns and a width of 200 to 500 microns is etched, and the flow channel branching angle is 60 to 90 degrees; at the same time, a hexagonal honeycomb support grid with a porosity of more than 85% is prepared, and the grid unit size is 500 to 800 microns; this structure increases the membrane stack flux by 30% and reduces the operating pressure difference to 60% of that of traditional membranes.
8. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S7, the composite membrane is immersed in an ethanol solution containing 1% triethylenetetramine and treated at a constant temperature of 55 to 65 degrees Celsius for 1.5 to 2.5 hours to induce secondary cross-linking between the amino groups and the residual epoxy groups; then, the composite membrane is alternately rinsed three times with 0.5 mol / L hydrochloric acid and sodium hydroxide solution, each rinse lasting 5 to 10 minutes, to activate the ion exchange groups and remove impurities; the absolute value of the zeta potential of the treated membrane surface is greater than 30 mV, and the ion exchange capacity reaches 1.8 to 2.2 milliequivalents / g.
9. The method for preparing a special ion bipolar exchange membrane according to claim 1, wherein: In step S8, the composite membrane was loaded into a three-compartment electrodialysis device for testing: using a 1 mol / L sodium chloride solution, an operating voltage of 25 V, a current density of 50 mA / cm2, and an operating temperature of 35 degrees Celsius; The measured current efficiency was 95% to 98%, the water dissociation voltage was stable at 0.68 to 0.72 volts, and the membrane resistance increased by less than 5% after 500 hours of continuous operation. Finally, the diaphragm was placed in a titanium alloy frame and encapsulated with a silicone sealing ring with a thickness of 0.5 to 1 mm. The torque of the frame bolts was controlled at 2 to 3 Nm to ensure long-term leakage-free operation.
10. A special ion bipolar exchange membrane, characterized in that: The exchange membrane is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method and application of high-thermal-conductivity PET water-blocking tape
CN120863013A